Analisis Singkatan Dan Simbol Terhadap Formulir Discharge Summary Rawat Inap Untuk Penilaian Akreditasi Snars Mirm (12) Periode Februari Di Rumah Sakit Pusat Pertamina Jakarta Selatan - Livia Nuri Syafitri; Demiawan Rachmatta Putro Mudiono; Sustin Farlinda; Djasmanto Djasmanto (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
Recording in SNARS Edition 1 is included in the Hospital Management Standards group on Information and Record Management (MIRM), one of the medical standards in MIRM, namely the standardization of diagnosis codes, procedure/action codes, symbols, abbreviations, and their meanings contained in the MIRM 12 standard. Where in the assessment element, the hospital must have regulations on standardizing diagnosis codes, procedure/action codes, definitions, symbols used and which should not be used, abbreviations used and which should not be used, and monitored their implementation. Pertamina Central Hospital is a referral hospital and accredited B. Where this hospital becomes the Presidential Hospital. Medical Records used in the form of Electronic and Manual Medical Records. On the Medical Record Form in the application there are abbreviations and symbols. In the use of abbreviations and symbols, socialization has been carried out which contains a guideline entitled "The RSPP abbreviation list book" but in its implementation no evaluation has been carried out. And also there are SOPs that state the existence of abbreviations, symbols, actions and diagnostic codes. In the period of February, there were 463 hospitalized patients. And researchers took samples of medical record number 132 medical records from 30% of the number of inpatients using the formula of slovin. This is a qualitative research using direct observation and documentation methods. The results of observation and study documentation show that the abbreviations that are not appropriate are 45%, 67% for symbols and 55% appropriate for summary form releases, The book of abbreviations and symbols belonging to Pertamina Central Hospital has not yet been legalized and socialized legally. And there is no SOP in accordance with SNARS MIRM 12 for abbreviations and symbols at Pertamina Central Hospital. There is also no evaluation in the implementation of the use of abbreviations and symbols as well as the books used, there are still not several symbols and abbreviations listed in the abbreviation and symbol guidelines in the Rspp.